Multilingual Semantic MediaWiki for Finno-Ugric dictionaries - Laxström, Niklas; Kanner, Antti (Septentrio Conference Series, 2015)
This paper introduces the concept of Multilingual Semantic MediaWiki, which can be used to build collaborative on-line projects for certain types of multilingual content. Namely, dictionaries whose users are multilingual or have different native languages. We describe two multilingual on-line dictionary projects built using the Multilingual Semantic MediaWiki framework. These projects cover Finnish, Swedish, the Sámi languages, Estonian and Ludic among others. We describe the benefits of using semi-structured data and the limitations of this particular semantic software based on the case study offered by the aforementioned projects. We evaluate these projects in terms of development and maintenance effort, number of visitors and contributors. We conclude that this is a low cost approach to increase openness and collaboration and to create more value for this kind of data.